ORLNC1 Suppresses Cell Growth in HER2-Positive Breast Cancer via miRNA-296 Sponging - Cheng, Xueyuan; Huang, Zhong; Pan, Anchao; Long, Di (Current Molecular Medicine, 2023)
Background: Accumulating research has demonstrated that aberrant levels of long noncoding RNAs (LncRNAs) are related to cancer progression. The effects of ORLNC1 in HER2+ breast cancer have yet to be explored. Methods: Real-time PCR was used to examine the expression of LncRNA ORLNC1 in HER+ breast cancer. CCK-8, wound healing and cell invasion assays were used to examine the effect of LncRNA ORLNC1 on HER+ breast cancer cells. Luciferase reporter assay was utilized to determine the regulatory relationship between LncRNA ORLNC1 and miR-296. Western blotting was used to measure the expression of PTEN. Xenograft mouse model was used to examine the effect of LncRNA ORLNC1 on tumor progression in vivo. Results: In this study, our findings revealed downregulation of ORLNC1 in HER2+ breast cancer specimens and cell lines. Low levels of ORLNC1 were related to poor prognosis and advanced cancer stage. Using gain- and loss-of-function assays, the ability of these tumor cells to proliferate was found to be inhibited by ORLNC1 in vitro and in vivo. Further analyses revealed that miR-296/PTEN axis is directly targeted by ORLNC1. Consequently, over-expression of miR-296 efficiently abrogated the upregulation of PTEN induced by ORLNC1, suggesting that ORLNC1 positively regulates PTEN expression by competitively binding to miR-296. Conclusion: Our results indicate that lncRNA ORLNC1 acts as a tumor suppressor by regulating the miR-296/PTEN axis in HER2+ breast cancer.
Keywords: PTEN